If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1(x + -1(x + -3)) = -1 Reorder the terms: 3x + -1(x + -1(-3 + x)) = -1 3x + -1(x + (-3 * -1 + x * -1)) = -1 3x + -1(x + (3 + -1x)) = -1 Reorder the terms: 3x + -1(3 + x + -1x) = -1 Combine like terms: x + -1x = 0 3x + -1(3 + 0) = -1 3x + -1(3) = -1 Multiply -1 * 3 3x + -3 = -1 Reorder the terms: -3 + 3x = -1 Solving -3 + 3x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3x = -1 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = -1 + 3 3x = -1 + 3 Combine like terms: -1 + 3 = 2 3x = 2 Divide each side by '3'. x = 0.6666666667 Simplifying x = 0.6666666667
| 3x-4+5x-12=180 | | (252)1/5 | | 8(t-4)+4t=4(3t+5)-10 | | 10(x-1)+4=12x | | 3*x-7=4*4+2 | | 8-2(t+5)=-2t-2 | | 3x/2-(x-1)/3=x/6 | | 6t+26=19t | | 3(y-7)=4(4+2) | | 8-2(t+5)= | | .2(x+3)-.5(x+3)=-.3x-.9 | | (5x-7)=(4x-6) | | 9x-2(2x+3)=x-4 | | -4(-9+x)=8 | | 2x-3(-2x+4)=13+x | | 2lnx=ln(10-3x) | | 3y+-8=y | | 5x^2-25=20x | | -3(6x+7)=-57 | | -5+0.5a=4 | | -3x+25=76 | | 11x-1/4 | | 10x-500=0 | | 2(2)-3y=12 | | -5x+4=-51 | | x^2+13x-5=0 | | 100*q=8.6145 | | 3ab/3ab= | | (x-19)(x+17)= | | 9x+5=167 | | 2t-5j=6t+3 | | B^2-13b=-42 |